A house full of stories - Axell, Anton (My University, 2024)
This thesis explores value and heritage in an urban context and what role it can play in sustainable development. Spanning from discourse on urban development and value management to a finished architectural proposal, the thesis is developed trough a critical discussion on urban development and value. The thesis is written within the studio Building Design and Transformation for Sustainability and aims to discover the beauty the lies within the environmental turn and explore the boundary between preservation and transformation, patina and decay. This thesis is site-specific and based on a listed building in central Gothenburg, which has undergone various periods of use and renovation but currently finds itself in a void, between the development of the area and the building’s own history. The development of the architectural proposal evolves through discussion of value management and through analysis of the building’s existing structure and character. The overall aim of the thesis is to contribute to the discussion on urban development and on what is considered worth preserving in an era where the building industry is dominated by growth and profit instead of improvment and adoptation. The discussion is based on various theorists, using theories from Helena Mattsson and Jil Stoner to William Morris and John Ruskin among others. This thesis seeks for the subtile changes, and finding the balance between the intangible, subjective values and spatial interventions. This thesis also aims to find a humanistic approach to sustainability and architecture, where the exploration and adaptation of a building’s current state play a significant role. The method is shaped by an iterative design driven research and critical theory building. The outcome is an architectural proposal to the buildings continuous management and usage, suggesting both preservation and transformation as a design strategy.
Keywords: Heritage, Preservation, Value, Public Space